Etiologies of Ischemic Stroke in Sub-Saharan Africa, Case of Benin - HOUINATO, Dismand (My University, 2020)
The purpose of our study was to investigate etiologies of ischemic stroke in the neurology university clinic of CNHU-HKM, Cotonou. Method: It was a cross-sectional, prospective and analytical study carried out from 1st November 2014 to 31st August 2015 in the neurology university clinic of CNHU-HKM. We included all patients with stroke whose ischemic nature was confirmed through brain CT scan or magnetic resonance imaging. Data analysis was conducted with Census and Survey Processing System (CSPRO). We carried out bivariate then multivariate analysis in identifying associated factors. Threshold value is estimated at p < 0.05. Results: 104 ischemic stroke patients participated in the study, representing 59.4% of all types of stroke. Mean age was 61.9 ± 12.3 years [26 - 87 years] with 1.6 as sex ratio. Among vascular risk factors, hypertension accounted for 85.6% of stroke cases. 29.8% suffered from aphasia. Embolic heart diseases and atherosclerosis were predominant, in a proportion of 53% and 26% respectively. Atrial Fibrillation (AF) accounted for 82% of embolic heart diseases. Conclusion: Etiologic investigation of stroke is important and should be systematically carried out. This study enabled to corroborate atherosclerosis predominance in etiologic investigation of ischemic stroke. Patients’ outcome could be improved by promptly managing the etiology through adoption of appropriate treatment.
Keywords: Ischemic Stroke; Etiologies; Benin; Africa